The Influence Aggregates Artificial to The Strength Concrete - Andi Yusra; Inseun Yuri Salena; Heri Safrizal (Budapest International Research and Critics University, 2020)
This study was conducted to investigate the effect of using aggregates artificial that is clay soil as partial substitution for coarse aggregates in concrete by determine the mass of concrete and its effect on the compressive strength. The proportion of aggregate artificial in design mix is 0%, 10%, 20%, and 30% with w/c ratio 0.3 and 25 MPa in strength design. The study used cylinder sample at test age 28 and 56 days. The weight of aggregates artificial is 12.97 kg and 13.05 kg for 0% subtitution, 12.07 kg and 12.12 kg, 10% subtitution, 11.45kg and 11.58kg (20%) and 10.95 kg and 11.17 kg, 30% subtitution. The test result in 0 % used aggregates artificial obtained strength concrete is 25.67 MPa and 25.95 MPa, 23.40 MPa and 23.87 MPa (10% used aggregates artificial), 18.02 MPa and 18.49 MPa (20% used) and 15.29 MPa and 15.85 MPa (30% used aggregates artificial). The results indicated that the higher the percentage in ALWA, the less the weight of concrete. Variation in aggregates artificial percentages affected the compressive strength, but in concrete ages, it did not have effect. However, the strength of the concrete may decrease, but still can be used as a structural concrete with a lighter weight of concrete.